LEISURE REPRESENTATIONS AND PRACTICES OF PHYSICAL EDUCATION UNIVERSITY PROFESSORS (Fiep Bulletin - online, 2011)
Teacher is the influential key of curriculum and pedagogy in the classroom, with strong consequences for education and human development and we believe that university teachers can help create a better reality of education in various levels, especially because they are teacher trainers. Therefore, the thinking and acting of these professionals, is crucial for the improvements and changes in the educational system. This research holds in professors of physical education and aims to identify their representations and practices in various dimensions: personal, professional, social and leisure, which have been investigated in two contexts: professional and leisure. The main objective is to assist in the construction of knowledge that can be useful in understanding the profession and teacher training in the area. For this paper, we chose to emphasize the professors' representations and practices of leisure, especially because we believe in the relevance of time and leisure practices in thinking and acting of human being. This is an interpretive study, based on interviews and observations, materialized in lives history. The framework of investigation consisted of four considered by their peers and students competent (good professors) university professors, among other characteristics, based on an intentionality that assumed that the professor should be a positive example for their students considering the high rate learning by modeling. The study shows that the boundary between work and leisure is tenuous, especially because the work of professors surveyed involves creation, innovation, discovery and satisfaction. We conclude that the work of the intellectual type, as is the case of these professors, which are common in situations where social time (work and leisure) are not so defined, this interaction between work and leisure is natural and easily found in the searched reality.
Keywords: Representations; Practices; Leisure